CDSDv: A compact database for the modeling of high-temperature CO2 radiation. (April 2020) - Vargas, João; Lopez, Bruno; Silva, Mário Lino da
Highlights: A vibrationally-specific database has been produced on the basis of CDSD4000. The database has a compact size (16MB) and produces fast spectral simulations when coupled to an adaptive lineshape routine. The resulting numerical routines allow full range spectral simulations for hot, nonequilibrium CO 2 . The code is validated against reference high-temperature CO 2 infrared spectra, evidencing limited loss of accuracy. Graphical abstract: Emission and absorption coefficients of one atmosphere of pure CO 2 at 3000K calculated with CDSDv Abstract: The Carbon Dioxide Spectral Databank 4000 is tailored for radiative transfer applications relevant for Mars atmospheric entry studies. This is carried out through the refitting of the original database, encompassing individual rovibrational transitions, into a more compact form where rotational transitions for specific vibrational bands are obtained through traditional polynomial expressions, fitted to the levels and transitions of the original database. This originates a certain loss of precision since the fitted expressions do not always reproduce the original data with full accuracy, namely for the perturbed transitions. This is offset by a more compact database suited for wideband radiative transfer simulations. This CDSDv database also provides some minor advantages, such as enabling the thermodynamic use of two-temperature ( T, Tv ) models and the determination of vibrational Einstein coefficients A v ′ v ″ which may be used in state-to-state kinetic models.